Burden of vertigo at home: Risks for patients with vertigo. Issue 6 (June 2020) - Kimura, Yuri; Tsunoda, Atsunobu; Tanaka, Kumiko; Anzai, Takashi; Ikeda, Katsuhisa; Tsunoda, Reiko; Terasaki, Omi
Objective: We aimed to clarify the burden of vertigo in patients' homes. Methods: This was a questionnaire survey among patients with vestibular vertigo. Four main questions were prepared. Q1: Where did you first notice vertigo? Q2: Where have you had the most difficulty with vertigo in your home? Q3: Where do you have difficulty at present? Q4: What household equipment have you used as a countermeasure to prevent further problems with vertigo? Results: Sixty patients completed the questionnaire. Benign paroxysmal positional vertigo (BPPV) was most common among respondents, followed by Ménière's disease. Q1: Most patients with BPPV first noticed vertigo in the bedroom; patients with other diseases first noticed vertigo in the living room. Q2: Both groups previously had the most difficulty with vertigo in the same locations as in Q1; these differences were significant between Q1 and Q2. Q3: Both groups had the most difficulty on stairs. Q4: Handrails were the most often used equipment for vertigo in both groups. There was no significant difference between Q3 and Q4. Conclusion: Our data revealed that the locations of risks differ among patients with vestibular disorders. Handrails were considered the most important equipment to prevent problems with vertigo.